Low Carbon Technology Innovation, Carbon Emissions Trading and Relevant Policy Support for China’s Low Carbon Economy Development - Dou, Xiangsheng (International Journal of Energy Economics and Policy, 2017)
The key to solving increasingly serious environmental problems is comprehensively to promote low carbon economy (LCE) development, while LCE development needs the conditions of particular system and capacity. This paper builds a cone model to focus on the analysis of these basic factors of low carbon technology innovation, carbon emissions right trading, carbon finance and low carbon policy to provide a theoretical basis for China’s LCE practice. The results indicate that low carbon technology innovation is the basis for the LCE development, while carbon emissions right trading is the key to the LCE development. At the same time, the LCE development needs the corresponding conditions such as carbon finance and low carbon policies. Therefore, China should currently focus on these problems to promote the rapid development of low carbon economy. Keywords: Low Carbon Economy, Low Carbon Technology Innovation, Carbon Emissions Right Trading, Carbon Finance, Low Carbon Economy Policies JEL Classifications: Q38, Q54, Q56